2015
DOI: 10.1088/0004-637x/813/2/118
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Continuum Emission and Dense Gas Tracers in NGC 3627: Combining Jansky Vla and Alma Observations

Abstract: We present Karl G. Jansky Very Large Array (VLA) Ka band (33 GHz) and Atacama Large Millimeter Array (ALMA) Band 3 (94.5 GHz) continuum images covering the nucleus and two extranuclear star-forming regions within the nearby galaxy NGC 3627 (M 66), observed as part of the Star Formation in Radio Survey (SFRS). Both images achieve an angular resolution of 2 ′′ , allowing us to map the radio spectral indices and estimate thermal radio fractions at a linear resolution of 90 pc at the distance of NGC 3627. The the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 44 publications
7
50
1
Order By: Relevance
“…This is true for our new measurements in M51 (ρ SFE dense −σ HCN = −0.62), and it remains true when we include the values for other galaxies from the literature (ρ SFE dense −σ HCN = −0.53). The trend goes in the same direction as that already pointed out by Murphy et al (2015) based on HCN emission in NGC 3627 (with three datapoints at ∼300 pc resolution), although there is a vertical offset between the trend in NGC 3627 and that in M51. Our measurements extend to the dense gas phase the result from Leroy et al (2017a), who already identified in M51 a correlation between the velocity dispersion and star formation efficiency of the bulk molecular gas traced by CO (using the full PAWS resolution, 40 pc), in the sense that larger linewidths are associated with lower star formation efficiencies.…”
Section: Trends With Stellar Mass Surface Densitysupporting
confidence: 83%
See 2 more Smart Citations
“…This is true for our new measurements in M51 (ρ SFE dense −σ HCN = −0.62), and it remains true when we include the values for other galaxies from the literature (ρ SFE dense −σ HCN = −0.53). The trend goes in the same direction as that already pointed out by Murphy et al (2015) based on HCN emission in NGC 3627 (with three datapoints at ∼300 pc resolution), although there is a vertical offset between the trend in NGC 3627 and that in M51. Our measurements extend to the dense gas phase the result from Leroy et al (2017a), who already identified in M51 a correlation between the velocity dispersion and star formation efficiency of the bulk molecular gas traced by CO (using the full PAWS resolution, 40 pc), in the sense that larger linewidths are associated with lower star formation efficiencies.…”
Section: Trends With Stellar Mass Surface Densitysupporting
confidence: 83%
“…Given that systematic offsets exist among the different SFR tracers used by the studies from the literature, we rescale those SFRs by an empirically derived factor to enforce consistency (see Appendix A for details). In NGC 3627, for the nuclear pointing in Murphy et al (2015) the HCN line was not fully covered by their spectral set-up, so we use the information from HCO + (1-0) instead in that particular case.…”
Section: Trends As a Function Of Stellar Mass Surface Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Before deriving the column densities, the integrated intensities are divided by the beam filling factor θ 2 source /(θ 2 source +θ 2 beam ), where θ source and θ beam are the source size and the FWHM of the telescope beam, respectively, to compensate for frequency dependence of the beam size. Here, the source size (θ source ) is assumed to be 10 ′′ , because distributions of HCO + (J = 1−0) are resolved to be ∼ 10 ′′ with ALMA in BE and NR (Murphy et al 2015). We assume the same source size in SA for simplicity.…”
Section: Column Densitiesmentioning
confidence: 99%
“…Constructing the star-formation history of the universe requires converting the synchrotron luminosities measured by low-frequency surveys to star formation rates via the tight, but empirical and local, far-infrared/radio correlation (de Jong et al 1985;Helou et al 1985;Yun et al 2001). Surveys at observing frequencies 10 GHz measure flux densities closer to the rest-frame frequencies n  30 GHz, where the total radio emission is dominated by the free-free radiation that is more directly proportional to the rate of massive star formation (e.g., Mezger & Henderson 1967;Turner & Ho 1983Klein & Graeve 1986;Kobulnicky & Johnson 1999;Murphy et al 2012aMurphy et al , 2015bNikolic & Bolton 2012), are still unbiased by dust emission or absorption, and yield higher angular resolution for a given array size.…”
Section: Introductionmentioning
confidence: 99%